Science of Salt: A regularly updated systematic review of salt and health outcomes studies (April to October 2018). Issue 8 (27th June 2019) - McLean, Rachael M.; Petersen, Kristina S.; Arcand, JoAnne; Malta, Daniela; Rae, Sarah; Thout, Sudhir Raj; Trieu, Kathy; Johnson, Claire; Campbell, Norman R. C.
Abstract: The Science of Salt reviews identify, summarize, and critically appraise published studies on dietary salt and health outcomes according to pre‐specified methods. This review covers the period April 3 to October 30, 2018. Here, nineteen studies that fit pre‐specified criteria for review and summary are included. Three of these, one prospective cohort study, one randomized controlled trial, and a post hoc analysis of the Dietary Approaches to Stop Hypertension (DASH) sodium trial fulfilled the quality criteria for detailed critical appraisal, including risk of bias assessment, and commentary. Two trials demonstrated a positive association between salt intake and blood pressure. In a cohort of older Italians, increased risk of total mortality was observed with salt intake less than ~16 g/d (6300 mg sodium/d) at baseline; no association existed for incident cardiovascular disease (CVD) or CVD mortality. The paucity of published studies which met our criteria for methodological quality is of concern.